Project performance rating model for water and wastewater treatment plant public projects - Abi Shdid, Caesar (2018)
Water and wastewater construction capital projects are distinctive, highly complex and do not currently have well-established overall performance rating models to assess their projects’ successes. Project performance used for gauging the overall success of project delivery is a complex concept that cannot be measured by one factor. It involves several criteria with many factors that need to be accounted for. Data from 43 water and wastewater projects delivered using the traditional design-bid-build (DBB) delivery method is collected to form a dataset that is utilized to build a project performance rating (PPR) model. The developed PPR model combines the key performance factors of a project into one performance index (PI). The PPR model is tested on a controlled case study project delivered by infusing certain integrated project delivery (IPD) principles into the DBB delivery method. The PPR model showed the implementation of the IPD principles to improve the performance of the case study project by a factor of 1.3. The developed model is a tool that helps utility owners compare the performance of various projects while getting a detailed insight into critical problem areas that are likely to impact performance rating.